Psychosocial factors associated with the risk of developing psychosis in a Mexican general population sample - Domínguez-Martínez, Tecelli; Sheinbaum, Tamara; Fresán, Ana; Nieto, Lourdes; López, Steven R.; Robles, Rebeca; Lara, Ma del Carmen; de la Fuente-Sandoval, Camilo; Barrantes-Vidal, Neus; Saracco, Ricardo; Franco-Paredes, Karina; Díaz-Reséndiz, Felipe; et al. (Frontiers in Psychiatry, 2023)
Epidemiological evidence has linked an array of sociodemographic and psychosocial factors with an increased risk of developing psychosis. However, research in samples from low- and middle-income countries is still scarce. This study used a Mexican sample to explore (i) sociodemographic and psychosocial differences between individuals with and without a positive screen for Clinical High-Risk for psychosis (CHR), and (ii) sociodemographic and psychosocial factors associated with screening positive for CHR. The sample consisted of 822 individuals from the general population who completed an online survey. Of the participants, 17.3% (n=142) met the CHR screening criteria. Comparisons between those who screened positive (CHR-positive group) and those who did not (Non-CHR group) showed that participants in the CHR-positive group were younger, had a lower educational level, and reported more mental health problems than the Non-CHR group. Furthermore, relative to the Non-CHR group, the CHR-positive group had a greater prevalence of medium/high risk associated with cannabis use, a higher prevalence of adverse experiences (bullying, intimate partner violence, and experiencing a violent or unexpected death of a relative or friend), as well as higher levels of childhood maltreatment, poorer family functioning, and more distress associated with the COVID-19 pandemic. Groups did not differ in sex, marital/relationship status, occupation, and socio-economic status. Finally, when examined in multivariate analyses, the variables associated with screening positive for CHR were: having an unhealthy family functioning (OR=2.75, 95%CI 1.69-4.46), a higher risk associated with cannabis use (OR=2.75, 95%CI 1.63-4.64), a lower level of education (OR=1.55, 95%CI 1.003-2.54), having experienced a major natural disaster (OR= 1.94, 95%CI 1.18-3.16), having experienced a violent or unexpected death of a relative or friend (OR=1.85, 95%CI 1.22-2.81), higher levels of childhood emotional abuse (OR= 1.88, 95%CI 1.09-3.25), physical neglect (OR=1.68, 95%CI 1.08-2.61), and physical abuse (OR=1.66, 95%CI 1.05-2.61), and higher COVID-related distress (OR=1.10, 95%CI 1.01-1.20). An older age was a protective factor for screening positive for CHR (OR=0.96, 95%CI 0.92-0.99). Overall, the findings highlight the importance of examining potential psychosocial contributors to psychosis vulnerability across different sociocultural contexts to delineate risk and protective processes relevant to specific populations and better target preventive intervention efforts.